Structural and optical properties of III-V nanowires and nanowire heterostructures grown by metalorganic chemical vapour deposition - Joyce, H; Gao, Q; Kim, Y; Tan, H; Jagadish, C (2007)
We have investigated the structural and optical properties of III-V nanowires grown by metalorganic chemical vapour deposition. Binary GaAs, InAs and InP nanowires, and ternary InGaAs and AlGaAs nanowires, have been fabricated and characterised. A variety of axial and radial heterostructures have also been fabricated, including GaAs/AlGaAs core-multishell and GaAs/InGaAs superlattice nanowires. GaAs/AlGaAs core-shell nanowires exhibit strong photoluminescence as the AlGaAs shell passivates the GaAs nanowire surface reducing the surface nonradiative recombination. © 2007 IEEE.